Effectiveness and tolerability of Perindopril plus Amlodipine single pill combination in Nigeria: The 13 City Hypertension Study - Ojji, Dike; Ansa, Victor; Ale, Boni; Sani, Mahmoud; Obasahan, Austine; Alagbe, Sola; Williams, Rotimi; Aknitomide, Tony; Okoye, Innocent; Umuerri, Ejiroghene; Nwafor, Eze; Mbakwem, Amam; et al. (SA Heart Journal, 2022)
Background: There is no large-scale study that has shown the efficacy of single pill combination (SPC) antihypertensive medications in black African population. We therefore evaluated the blood pressure (BP) lowering efficacy and the tolerability of Perindopril plus Amlodipine SPC in black African patients. Methods: It was a multi-centre, prospective, observational programme among hypertensive patients using different doses of Perindopril and Amlodipine. Primary endpoint was assessed as the change in mean sitting systolic and diastolic BPs from baseline to 3 months. Results: 937 patients (55.7% female) were analysed, and the mean age was 56.4 ± 12.7 years. Systolic and diastolic BPs were significantly reduced by 17.3/ 9.4mmHg, 21.1/10.8mmHg mmHg and 24.6/12.7mmHg at 4, 8 and 12 weeks respectively compared to baseline value (p<0.0001). Dry cough was seen in 0.64% and angioedema 0.1% of the patients. Conclusions: Perindopril plus Amlodipine SPC provided clinically meaningful BP reductions and is well tolerated in a black African population. SAHeart 2022;19:6-12